A MoS2-based coplanar neuron transistor for logic applications. (2nd May 2017) - Hu, S G; Liu, Y; Li, H K; Chen, T P; Yu, Q; Deng, L J
Abstract: The human brain is an extremely complex system of 10 10 –10 11 neurons. To construct brain-like neuromorphic hardware, the neuron unit should be implemented effectively. Here, we report a neuron transistor based on a MoS2 flake, which has summation and threshold functions similar to biological neurons and may act as a basic neuron unit in neuromorphic hardware. The neuron transistor is composed of a floating gate and two control gates. A heavily doped silicon substrate serves as the floating gate, while the two control gates are capacitively coupled with the floating gate. The neuron transistor can be well controlled by the two control gates individually or simultaneously. The drain current can be modulated by the input voltages at the control gates. While the current response of the neuron transistor has a large dependence on the magnitude of the input signal, it shows little dependence on the frequency of the input signal. To demonstrate the potential neuromorphic application of the neuron transistor, functions including abacus-like function, AND logic and OR logic are realized in the neuron transistor.